Recent Publications (Quarterly Journal of Economics, 1966)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 80, Issue 1, February 1966, Pages 161–165, https://doi.org/10.1093/qje/80.1.161 Published: 01 February 1966